포장재가 멸치조미가공품의 저장 중 이화학적 품질 특성에 미치는 영향 - 이의석(Eui-Seok Lee); 이형주(Hyong-Ju Lee); 배재석(Jae-Seok Bae); 김용국(Yong-Kuk Kim); 이종혁(Jong-Hyeouk Lee); 홍순택(Soon-Taek Hong) (東아시아食生活學會誌, 2013)
This research is performed to investigate the changes in the physicochemical properties and microbial growths of seasoned anchovies with various packaging materials (PET/CPP : polyethylene terephthalate/cast polypropylene, PET/EVOH : polyethylene terephthalate/ethylene-vinyl alcohol, PET/AL/LDPE: polyethylene terephthalate/aluminum/low density polyethylene), which are stored at various temperatures (25, 35, $45^{°}C$) for 60 days. Generally, it is being observed that changes in physicochemical properties (i.e., moisture content, color, brown intensity, TBA value, TMA, VBN etc) of seasoned anchovies are significant when stored at higher temperatures. Particularly, the packaging materials are found to influence substantially on the physicochemical properties of seasoned anchovies. With packaging materials of high oxygen transmission rates and moisture vapor transmission rates (i.e., PET/CPP), the changes in physicochemical properties of seasoned anchovies are significant, while being low with low oxygen transmission rates and low moisture vapor transmission rates (i.e., PET/EVOH). In addition, results of microbial growths in seasoned anchovies show that significant increases in total aerobic bacteria counts (about 100-fold after 60 day of storage) are observed in samples with packaging materials of high oxygen transmission rates and moisture vapor transmission rates (i.e, PET/CPP), while with only small increases for samples of low oxygen transmission rates and low moisture vapor transmission rates (i.e., PET/EVOH). Based on the changes in the physicochemical properties and results of microbial growths, it is being concluded that PET/EVOH film is suitable for the packaging of seasoned anchovies.